Evaluation of Child Cases Admitted for Tick Bite and Tick Species in İstanbul - Abdurrahman Avar Özdemir; Yakup Yeşil; Aynur Gülanber; İlker Efil (Galenos Yayinevi, 2018)
Aim:The Crimean-Congo Haemorrhagic Fever (CCHF) is a tick-borne infection that has a high mortality. In Turkey, the total number of cases reported between 2002-2014 was 9.069 and 440 of them died. The aim of this study is to evaluate the demographic characteristics of the children with the complaint of tick bite and to determine the species of the ticks seen in İstanbul.Materials and Methods:A hundred sixty two tick bite cases were analyzed with respect to demographic, clinical and laboratory findings between January and December 2014. The blood samples for whole blood count, prothrombin time, activated partial thromboplastin time, alanine aminotransferase, aspartate aminotransferase and creatinine were obtained from all cases and they were followed up for 10 days. The ticks removed from patients were classified by the Department of Parasitology in the Veterinary Faculty of İstanbul University.Results:The mean age of the patients was 6.1±3.7 years and 76% of them were male. Eighty four (52%) of the cases had additional complaints other than tick bite. The most frequently complaints were nausea/vomiting (26%), fever (19%) and cough (14%). We found that 34 (20%) of them had abnormal laboratory results such as elevated liver enzymes, leukocytosis, leukopenia, thrombocytopenia and prolonged prothrombin time. August was the month in which most patients applied (56 cases, 34%). The regions of body that were most bitten by the ticks were the extremities (35.8%). The total number of larvae, nymphs and adult ticks were found as 4, 88 and 14 respectively.Conclusion:This study showed that the tick species in the İstanbul province were largely different from the species causing CCHF. Although the incidence of CCHF in İstanbul is lower than in other regions of Turkey, children and their families who live in or travel to rural areas in Istanbul should be informed about this disease.